Low expression of microRNA‐340 confers adverse clinical outcome in patients with acute myeloid leukemia - Wang, Qi; Feng, Tao; Xu, Jun; Miao, Mei‐Hua; Ji, Xue‐Qiang; Zhu, Hong; Shao, Xue‐Jun (Journal of cellular physiology, 2019)
MicroRNA‐340 (miR‐340) was considered as a tumor suppressor by affecting cancer cell proliferation, apoptosis, invasion, and migration, and was downregulated in diverse cancers. Moreover, dysregulation of miR‐340 was also found to be associated with drug resistance and predicted patients’ survival in various cancers. Herein, we investigated miR‐340 expression and its clinical significance in acute myeloid leukemia (AML). Real‐time quantitative polymerase chain reaction was performed to detect miR‐340 expression in bone marrow (BM) from 99 newly diagnosed AML patients except for acute promyelocytic leukemia (APL), 19 AML patients achieved complete remission (CR), and 29 healthy donors. BM miR‐340 expression was significantly underexpressed in newly diagnosed AML patients as compared with controls (p = 0.031) and AML patients achieved CR (p = 0.025). No significant differences were observed between miR‐340 expression and most of the clinicopathologic features (p > 0.05). However, low miR‐340 expression was found to be associated with lower CR rate in both non‐APL‐AML and cytogenetically normal AML (CN‐AML; p = 0.001 and 0.031, respectively), and acted as an independent risk factor for CR by logistic regression analysis (p = 0.001 and 0.021, respectively). More important, among both non‐APL‐AML and CN‐AML, low expression of miR‐340 was also associated with shorter overall survival (OS; p = 0.013 and 0.005, respectively), and was further validated by Cox regression (p = 0.031 and 0.039, respectively). Collectively, our study showed that BM miR‐340 expression was downregulated in AML, and low expression of miR‐340 correlated with adverse prognosis. Our study showed that bone marrow miR‐340 expression was downregulated in acute myeloid leukemia, and low expression of miR‐340 correlated with adverse prognosis.